PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - Luthain, Namira Dinda (Departemen Matematika, 2023)
Good math problem solving skill is expected in math. Students' mathematical problem-solving skills are inadequate, according to observational tests. This can result from studying that doesn't enhance mathematical problem solving. Realistic Mathematics Education (RME) applied as the solution of problems. Quasy-experimental that using a Nonequivalent Posttest-Only Control Group Design, is used in this research. Hypothesis testing yielded p-value 0.005. As the p-value is <0.05, is rejected in the hypothesis test. This indicates that class VIII.3 students who use the RME approach solve mathematical problems better than class VIII.5 students who use conventional learning.Keywords. –Mathematical Problem-Solving Skill, Realistic Mathematics Education (RME)